Саяси тұрақтылық мәселесі қоғамның модернизациялануы процесінде маңызды орынға ие. (Journal of Philosophy, Culture and Political Science, 2018)
The problem of maintenance of Political permanent is actual case in the conditions of modernization. That is why the factors of maintenance of political permanent were analysed in the article.